A Pragmatic Analysis Of Directive Utterances In The Translation Of Holy Al-Qur'an Particularly On The Verses OfFive Pillars Of Islam - Ningsih, Desy Nur Wahyu, Agus Wijayanto, Ph.D, Siti Zurhriah Ariatmi, M. Hum (2014)
This research is aimed of describing the intention and describing the form of directive utterance. The object is directive utterances. The data are sentences containing directive intention in the English translation of Holy Al-Qur'an particularly on the verses of five pillars of Islam. In collecting the data, the writer uses documentation method by selecting the directive utterance in the English translation of Holy Al-Qur'an particularly on the verses of five pillars of Islam. To describe the illocution, the writer uses pragmatic approach especially speech acts of Kreidler's theory. While to describe the form the writer refers to Frank's theory. The result of the study shows that (1) there are three types of intention that found in the data; they are intention of commanding (71%), the intention of prohibiting (26%), and the intention of requesting (3%). There are two types of sentence that can be found in the data the first is imperative sentence (83%) and the second is declarative sentence (17%).